Guy Debord y los situacionistas. El auge de la vida cotidiana en los albores de Mayo de 1968. - Arranz Guilarte, Marina (Historiografías, 2022)
Abstract This article analyses the transference of creativity to everyday life in the second half of 20th century through the work and praxis of the situationist author Guy Debord and his contributions to fields such as cinema, urbanism, social theory, and political activism, in the context of the events of 1968. That year is regarded as a turning point in the concept of politics and the value system that prevails in western society. From then on, politics shall include everyday life, while the value system will not be given externally, but as a realm where everyone holds the responsibility of searching a meaning for life. Debord is a key author to understand both changes. Key Words Guy Debord, situationists, everyday life, spectacle, situation